Pengaruh Religiusitas Terhadap Pemilihan Pakaian pada Wanita Muslim - Ivon Sandya Sari Putri (Jurnal Riset Bisnis dan Investasi, 2020)
This research provides information about religiosity matter toward Muslim women’s behavior in clothing selection. From 339 data respondents using regression analysis, it showed that religiosity has a negative effect on clothing brand attributes and Muslim women consider the comfort of clothing elements more. From the result of this study, it looks like a great opportunity for potential entrepreneurs who don’t have a popular brand yet to enter the Muslim women’s clothing industry.